The distribution of rennet activity between the cheese aging process and whey is not influenced by the association of enzymes with caseins - Seyed Mehrdad Mirsalami; Mahsa Mirsalami; Afshar Alihosseini; Amin Ghodousian (Heliyon, 2024)
The division of rennet in cheesemaking is split between the curd and whey, influencing the taste and texture of aged cheeses. Our study aimed to examine how raising the protein concentration in reconstituted skim milk (up to 8.8 %) affects the distribution of calf rennet activity (RA) in rennet curds produced through two methods: renting only and renneting with glucono-δ-lactone (GDL) to achieve slow acidification. The distribution of rennet activity (RA) into curds increased as the concentration of skim milk rose, ranging from 8.6 % to 29.1 % without acidification, and from 6.5 % to 19.4 % when combined with slow acidification. This increase seemed to be related to the retention of moisture and protein. Surprisingly, the concentration of residual RA in the whey (measured in international milk clotting units, IMCU/mL) remained unaffected and remained consistent with the initial IMCU/mL of milk. This suggests that the division of RA between curd and whey is not influenced by the association of enzymes with caseins (CNs). Instead, it is possible that the strength of interactions between CNs themselves plays a significant role. These findings could be valuable for research focused on enhancing the cheese aging process.